ACOUSTIC SONICATION EFFECTS ON SEWAGE SLUDGE DISINTEGRATION - Tuan, Le Ngoc; JULCOUR-LEBIGUE, Carine; DELMAS, Henri (Vietnam Journal of Science and Technology, 2015)
This work aimed at investigating the effect of audible frequency (FS = 12 kHz) on sludge pretreatment by sonication (US) under pressure for the first time. The main US parameters (power -PUS, intensity -IUS) were also looked into. The higher PUS, the higher sludge disintegration (DDCOD) was achieved due to the increase in cavitation intensity, e.g. at 7000 kJ/kgTS, DDCOD improvement was about 74% when increasing PUS from 50 to 360 W (IUS of 5.2-37.4 W/cm2). In addition, about 16% of DDCOD improvement was achieved when switching from 50W-SP to 360W-BP at same IUS (about 37.5 W/cm2). Besides, sludge disintegration was significantly improved by low frequency US (12 vs. 20 kHz) due to more violent cavitation: by 64% at ES of 7000 kJ/kgTS.  Positive effect of pressure associated with high PUS and low FS was also found. This work provided general information and trends related to sonication process to be used or checked in other potential applications of physical effects of acoustic cavitation.